Teknik Pengujian Equivalence Partions untuk Pengujian Aplikasi Sistem Penunjang Keputusan Pegawai Terbaik Menggunakan Black Box - Zuhair, Ahmad; Khadafi, Farhan; Andriansyah, Achmad Muzakih; Saputra, Bayu; Saifudin, Aries (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
The development of decision support system applications for the selection of the best employees is very important to support management in making decisions. This application must be free of errors because if there are errors can be detrimental to several parties, both the company and the employee. To guarantee that the floating application is error free, a test is needed. Testing on an application aims to check whether a program is running properly or there are still errors that must be corrected so that the program created will be a program that has good quality. The testing technique consists of White Box Testing and Black Box Testing which are widely used by testers to check the program is appropriate or not. The Best Employee Decision Support Application will be tested using Black Box Testing where the test only aims to see whether the program is in accordance with the function desired by the program without knowing the program code used. Types of testing of the various Black Box methods, one of which is the Equivalence Partitions used by the authors in this study. Equivalence Partitions Technique is a test based on data entry on each form in the Best Employee Decision Support System, each input menu will be tested and grouped according to function whether it is valid or invalid. With this test the quality of the software created can be expressed objectively very well and has fulfilled all the requirements set.